NLRP3 Inflammasome and Allergic Contact Dermatitis: A Connection to Demystify - Sebastião, Ana Isabel (2020)
Allergic contact dermatitis is a common occupational disease that manifests as a cell-mediated hypersensitivity reaction following skin exposure to small reactive chemicals termed haptens. Haptens penetrate the stratum corneum and covalently modify proteins in the epidermis, inducing intracellular stress, which further leads to the release of damage-associated molecular patterns (DAMPs), such as uric acid, reactive oxygen species, hyaluronic acid fragments and extracellular adenosine triphosphate (ATP). These DAMPs are recognized by pattern recognition receptors (PRRs) in innate immune cells, namely dendritic cells (DCs), leading to their maturation and migration to the draining lymph nodes where they activate naïve T lymphocytes. Among all PRRs, several studies emphasize the role of NOD-, LRR- and pyrin domain-containing protein 3 (NLRP3) inflammasome on the allergic contact dermatitis (ACD) sensitization phase. However, skin allergens-danger signals-NLRP3 inflammasome axis is yet to be completely elucidated. Therefore, in this review, we sought to discuss the molecular mechanisms underlying DAMPs release and NLRP3 inflammasome activation triggered by skin allergens. The elucidation of these key events might help to identify novel therapeutic strategies for ACD, as well as the development of nonanimal alternative methods for the identification and potency categorization of skin sensitizers.